Relationship Of Testosterone Levels In Males With Coronary Heart Disease - MAMTA SETH,; ASHUMA SACHDEVA,; PRASANTA SAHAROY,; SHASHI SETH,; HIMANSHU MADAAN, (International Journal of Pharma and Bio Sciences, 2011)
Males are more than twice at the risk of dying from coronary disease than women. The finding that estrogen has a protective role in females led to the speculation that testosterone is deleterious to the male cardiovascular system and contributes to the vascular risk, but subsequent research showed little evidence that endogenous testosterone is an adverse risk factor, but the role of testosterone status and replacement therapy on male health is controversial. We studied the levels of testosterone in 60 males with recent coronary heart disease confirmed by the levels of troponin I ultra and compared them with the age matched controls from normal population. These parameters were assayed using chemiluminescent technology. We found that in males with CHD the testosterone levels were significantly reduced. This article discusses the cardioprotective role of testosterone in males.